178k views
5 votes
1/2 (x−8)+1=2( 1 8 x−1)

User Bob Ebert
by
5.2k points

1 Answer

1 vote

Answer:

The solution for the given algebraic equation is
( - 2)/(71)

Explanation:

Given algebraic equation as :


(1)/(2) ( x - 8 ) + 1 = 2 ( 18 x - 1 )

Now solving the equation while opening the brackets

So,
(1)/(2) × x -
(1)/(2) × 8 + 1 = 2 × 18 x - 2

Or,
(x)/(2) -
(8)/(2) + 1 = 36 x - 2

or,
(x)/(2) - 4 + 1 = 36 x - 2

or,
(x)/(2) - 3 = 36 x - 2

or,
(x)/(2) - 36 x = - 2 + 3

Or,
(x)/(2) - 36 x = 1

or,
(x - 72 x)/(2) = 1

or,
(- 71 x)/(2) = 1

∴ 71 x = - 2

I.e x =
( - 2)/(71)

Hence The solution for the given algebraic equation is
( - 2)/(71) Answer

User MCSI
by
5.5k points